A Topological Cluster of Differentially Regulated Genes in Mice Lacking PER3 - Van der Veen, Daan R.; Laing, Emma E.; Bae, Sung-Eun; Johnston, Jonathan D.; Dijk, Derk-Jan; Archer, Simon N. (Frontiers in Molecular Neuroscience, 2020)
Polymorphisms in human circadian clock gene PERIOD3 (PER3) are associated with a wide variety of phenotypes such as diurnal preference, delayed sleep phase disorder, sleep homeostasis, cognitive performance, bipolar disorder, type 2 diabetes, cardiac regulation, cancer, light sensitivity, hormone and cytokine secretion, and addiction. However, the molecular mechanisms underlying these phenotypic associations remain unknown. Per3 knockout mice (Per3-/-) have phenotypes related to activity, sleep homeostasis, anhedonia, metabolism, and behavioural responses to light. Using a protocol that induces behavioural differences in response to light in wild type and Per3-/- mice, we compared genome-wide expression in the eye and hypothalamus in the two genotypes. Differentially expressed transcripts were related to inflammation, taste, olfactory and melatonin receptors, lipid metabolism, cell cycle, ubiquitination, and hormones, as well as receptors and channels related to sleep regulation. Differentially expressed transcripts in both tissues co-localised with Per3 on an ~8Mbp region of distal chromosome 4. The most down-regulated transcript is Prdm16, which is involved in adipocyte differentiation and may mediate altered body mass accumulation in Per3-/- mice. eQTL analysis with BXD mouse strains showed that the expression of some of these transcripts and also others co-localised at distal chromosome 4, is correlated with brain tissue expression levels of Per3 with a highly significant linkage to genetic variation in that region. These data identify a cluster of transcripts on mouse distal chromosome 4 that are co-regulated with Per3 and whose expression levels correlate with those of Per3. This locus lies within a topologically associating domain island that contains many genes with functional links to several of the diverse non-circadian phenotypes associated with polymorphisms in human PER3.